Influence of extra training means on effectiveness of fencers` technical tactic actions - Lopatenko, G. O. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2016)
Purpose: to determine influence of the worked out extra training means` complex on effectiveness of realization of elite sportsmen`s competition functioning components. Material: in the research 12 fencers participated. The researches were conducted in the morning, against the background of organism`s recreation. Before sportsmen`s duel we applied two types of pre-competition warming up: traditional and experimental. Video recording was fulfilled with video camera Samsung HMX-S15. Results: we calculated volume, effectiveness and efficiency of sportsmen`s actions in fights with different opponents and in different situations of duel. We showed possibility of extra training complexes` application, oriented on mobilization of workability in the process of direct pre-start preparation of elite sportsmen. Such exercises considered main actions and organism`s typical responses in the process of competition functioning. Conclusions: Consideration of typolical (for fencing) organism`s responses and peculiarities of competition functioning structure influence positively on indicators of sportsmen`s competition functioning.